Protecting the Public's Health in Pandemics: Reflections on Policy Deliberation and the Role of Civil Society in Democracy - Morrissey, Mary Beth Quaranta; Rivera-Agosto, Jorge L. (Frontiers in Public Health, 2021)
The COVID-19 pandemic (“the pandemic”) has magnified the critical importance of public policy deliberation in public health emergency circumstances when normal health care operations are disrupted, and crisis conditions prevail. Adopting the lens of syndemic theory, the disproportionate impact of the pandemic on vulnerable older adults suggests that the pandemic has heightened pre-existing precarities and racial inequities across diverse older adult populations, underlining the urgency of needed policy reforms. While the pandemic has called attention to systemic failures in U.S. public health emergency planning at both federal and state levels of government, the important role of civil society in influencing policy decision making and advocating for legal and ethics reforms and social change in a democracy calls for more open dialogue in aging, public health and legal communities and constituencies. To foster this dialogue, one public health lawyer, who is also a bioethicist and gerontological social work researcher and served as chair of the New York State Bar Association Health Law Section COVID Task Force in 2020 (“Task Force”), shares her first-person perspectives on the process of leading the development of a statewide bar's recommendations for policy reforms, including the challenges and conflicts encountered. A hospital-based attorney and clinical bioethicist brings a clinical ethics perspective to the discussions. This first-person contribution discusses the power of constituencies to influence policy deliberation in a democracy, and the implications of the Task Force recommendations for future aging and public health policy, particularly in view of the high suffering burdens and trauma older persons and older people of color have borne during the pandemic.